2003
DOI: 10.1074/jbc.m300092200
|View full text |Cite
|
Sign up to set email alerts
|

Rigidity of Collagen Fibrils Controls Collagen Gel-induced Down-regulation of Focal Adhesion Complex Proteins Mediated by α2β1 Integrin

Abstract: Previous studies have shown that collagen gel overlay induced selective proteolysis of focal adhesion complex proteins in Madin-Darby canine kidney (MDCK) cells. In this study, we examined whether morphological and biochemical changes were present in cells cultured on collagen gel. We found that focal adhesion complex proteins, including focal adhesion kinase (FAK), talin, paxillin, and p130cas , but not vinculin, were decreased within 1 h when MDCK cells were cultured on collagen gel. Collagen gel-induced sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
45
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 45 publications
6
45
0
Order By: Relevance
“…The present study confirms and extends our previous studies to demonstrate that MT1-MMP stimulates ERK activation in 3-D collagen, which is indispensable for proliferation of cancer cells. It is well documented that the interaction between collagen fibrils and integrin α 2 β 1 generates the growth-suppressive signals in normal epithelial or cancer cells cultured in 3-D collagen [7,[20][21][22], which can be abrogated by pericellular collagenolysis [14,15]. We represent that MT1-MMP induces c-Src activation in 3-D collagen by modulating extracellular microenvironment, which subsequently activates paxillin to scaffold signaling molecules for ERK pathway and thus leads to escape cells from growth-suppressive signals.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…The present study confirms and extends our previous studies to demonstrate that MT1-MMP stimulates ERK activation in 3-D collagen, which is indispensable for proliferation of cancer cells. It is well documented that the interaction between collagen fibrils and integrin α 2 β 1 generates the growth-suppressive signals in normal epithelial or cancer cells cultured in 3-D collagen [7,[20][21][22], which can be abrogated by pericellular collagenolysis [14,15]. We represent that MT1-MMP induces c-Src activation in 3-D collagen by modulating extracellular microenvironment, which subsequently activates paxillin to scaffold signaling molecules for ERK pathway and thus leads to escape cells from growth-suppressive signals.…”
Section: Discussionmentioning
confidence: 75%
“…In contrast, cultivation in three-dimensional (3-D) collagen suppresses the proliferation of numerous cell types. This growth-suppressive signal may be mediated by integrins, as integrin α 2 β 1 mediates fibril collagen-induced inhibition of cell growth [6] and 3-D collagen induces down-regulation of cell-matrix adhesion proteins such as FAK, talin, and paxillin, which is blocked by integrin α 2 β 1 -neutralizing antibody [7]. Recent study has demonstrated that reduction of cell-matrix adhesion in 3-D ECM causes growth inhibition [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, by means of the collagenase treatment, we were able to dissolve the collagen gel and remove it from cell lysates. In previous studies, researchers often lysed the cells without TCA and collagenase treatment for WB (Wang et al 2003;Engler et al 2006;Tsutsumi et al 2009;Wu et al 2009). We refer to this approach as ''the conventional method'' in this study.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that substrate stiffness affects cell behavior. For example, the rigidity of a collagen matrix regulates collective motility and the expression of adhesion proteins (Wang et al 2003;Haga et al 2005). Furthermore, stiffer substrates may enhance cancer progression (Paszek et al 2005;Levental et al 2009).…”
Section: Introductionmentioning
confidence: 99%